“Finally my turn to write my story”: A convergent mixed methods study exploring the perceptions and experiences of emerging adults who aged out of foster care in Canada - Brianna Jackson; Margaret L. Holland; Victoria Smye; Sarah Lowe; Lois S. Sadler (PLoS ONE, 2025)
Background Each year, thousands of young Canadians ‘age out’ of foster care on or before their 19 th birthday. This abrupt transition to independence coincides with emerging adulthood (ages 18–29), a developmental period associated with transformational changes, including new or worsening mental health challenges. Objective The purpose of this study was to understand how emerging adults, who aged out of foster care in Canada, navigated their transition to independence, and specifically, how experiences of structural violence encountered pre- and post-emancipation may have influenced their mental health and capacity for positive adaptation. Participants and Setting 203 emerging adults from across Canada took part in the quantitative arm of this study, with a subsample of 31 participants enrolled in the qualitative arm. Virtual methods (online survey and video conferencing) supported remote participation. Methods A convergent mixed methods design involved concurrent quantitative and qualitative data collection and analysis, followed by integration of emergent findings. The quantitative arm of the study consisted of an electronic questionnaire including sociodemographic characteristics, foster care histories, and ten validated measures. The qualitative arm involved virtual semi-structured interviews regarding participants’ transition to independence upon aging out of care, including experiences and perceptions of structural violence, mental health challenges, and positive adaptation. Results Correlation analyses and regression modelling revealed relationships between and among structural violence, mental health challenges, and positive adaptation in this population. Nine qualitative themes uncovered the contextual nuances of participants’ transition to independence. Two joint displays were developed to visually represent the integration of quantitative and qualitative data. Conclusions By exploring this clinical issue from a combined socioecological, temporal, and intersectional perspective, key findings reflect its complexity, nuance, and transformative capacity. Integrated data may suggest approaches for future development of interventions to address the unique mental health care needs of this population.